Pengelolaan Stres Kerja Pada Karyawan Bank BTN UNIT CBC Palembang - Marsyah, Nadya; Itryah, Itryah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
The community service program was conducted from February to May 2025 at Bank BTN CBC Palembang Unit, Wholesale Trade Division (WTD). Based on direct observation and structured interviews on May 9, 2025, with two employees IR as Risk Head for eighteen years and RTY from Commercial Performance Division for thirteen years, work stress became a leading variable influencing employee wellbeing. Data collection revealed heavy workloads, tight deadlines, and insufficient social support as main stress causes. Both respondents manifested physical symptoms including digestive disorders, headaches, and sleep disorders plus psychological symptoms like irritability, concentration difficulties and anxiety. Other stressors are sudden changes in monthly targets with very short rest periods plus poorly communicated regulatory changes adding confusion and psychological pressure. They cope with stress independently using time management strategies, regular exercise, breathing techniques plus meditation. However, organizational support was still low with no formal stress management training, psychological counseling services or open communication forum between divisions. Work stress occurs when job demands exceed individual capacity to cope, resulting in physical and emotional reactions. This study proposes that BTN CBC Palembang Unit management establish an integrated psychological well-being program by providing internal counseling services, facilitating inter-divisional communication, and developing work-life balance policies toward creating a healthier and more productive working environment supporting long-term organizational goals.